Mobile game development with Unity 3D - Biswas, Raja (Packt, 2019)
"Compared to other engines, Unity provides easy portability to both iOS and Android, allowing for mass dissemination of a mobile game. You'll create your own adventure game using animations while fine-tuning your C# programming skills with intermediate concepts like class inheritance, abstract classes, and interfaces! You'll utilize the Singleton design manager to create powerful manager classes that help delegate actions in your game. By the end of this course, you will have experience with the complete mobile game development to testing! You will have a fully finished, downloadable game to add to your portfolio if you are pursuing mobile development professionally!You will leave this course with confidence in their ability to utilize the latest and greatest game development techniques and will be able to create, and publish their own unique Android mobile games!"--Resource description page